UNSTRESSED VOCALISM ALLOPHONIC VARIABILITY IN POLYSYLLABIC WORDS IN THE ENGLISH SPEECH OF UKRAINIANS - Варлаков, Антонина (SWorldJournal, 2020)
The research considers the results of auditory and acoustic analysis of unstressed English vocalism formant variability in the interfered speech of Ukrainian speakers. The relevance of the study is predetermined by the necessity of intercultural communica